1989
DOI: 10.1002/yea.320050308
|View full text |Cite
|
Sign up to set email alerts
|

5′‐Secondary structure formation, in constrast to a short string of non‐preferred codons, inhibits the translation of the pyruvate kinase mRNA in yeast

Abstract: The effects of poor codon bias and secondary structure formation upon the translation of the pyruvate kinase (PYK1) mRNA have been investigated in Saccharomyces cerevisiae. Following insertion mutagenesis at the 5'-end of the PYK1 coding region, the gene was transformed into yeast, and translation assessed directly in vivo by determining the distribution of the modified PYK1 mRNAs across polysomes fractionated by sucrose density gradient centrifugation. The chromosomally-encoded (wild-type) PYK1 mRNA, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Furthermore, the transcription factors encoded by value on lactate. Each assay ABFJ, GCRI, and RAP) are known to influence the expresassays on three independent sion of several glycolytic genes (3,7,13,15,61 (12,60,65).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the transcription factors encoded by value on lactate. Each assay ABFJ, GCRI, and RAP) are known to influence the expresassays on three independent sion of several glycolytic genes (3,7,13,15,61 (12,60,65).…”
Section: Resultsmentioning
confidence: 99%
“…The RNA was then transferred to Hybond-N membranes (64), UV fixed, and probed with either radiolabeled DNA fragments or oligonucleotides ( Table 1). The adaptions made to previously published hybridization and washing conditions (7,52) for each of the DNA or oligonucleotide probes are summarized in Table 1. Hybridizations were always performed under conditions of probe excess (56).…”
Section: Methodsmentioning
confidence: 99%
“…The ability of a stem-loop structure to block the progress of 40 S subunits along mRNA during "scanning" is believed to be a cause for translation inhibition in both yeast and mammalian cells (54). It has been shown that translation initiation in S. cerevisiae is very sensitive to the presence of stem-loop structures in the 5Ј-untranslated region (55,56). Therefore, the inhibitory effect of the potential rpl25-1 stemloop structure may be synergistic with absence of Cpc2.…”
Section: Discussionmentioning
confidence: 99%
“…lB), the 4.5-kbp EcoRI-Hind111 LYS2 fragment from pUKC 3 71 (donated by Mick Tuite; University of Kent, England), the 1.1-kbp Hind111 URA3 fragment from pSPUR1 (Brown et al, 1988), and the 1.5-kbp ACTZ fragment from pSPACT9 (Bettany et al, 1989).…”
Section: Probesmentioning
confidence: 99%